Hollywood and the Spanish Civil War: The Hidden Anti-Fascist Ideology of Love Under Fire (1937). - Guiralt, Carmen (Historical Journal of Film, Radio & Television, 2023)
When the Spanish Civil War (1936–1939) began, Hollywood immediately rushed to create screenplays about the conflict. However, only three fiction films were made during the course of the war: The Last Train From Madrid (James Hogan, Paramount Pictures, 1937), Love Under Fire (George Marshall, Twentieth Century-Fox, 1937) and Blockade (William Dieterle, Walter Wanger/United Artists, 1938). This article examines Love Under Fire, a production that has scarcely been studied and which remains commercially unavailable. The research has made it possible to establish that, despite its appearance as an inoffensive film that adheres to the Hays Office guidelines of impartiality, Love Under Fire is neither apolitical nor neutral, but has an anti-Franco, anti-Fascist and anti-Nazi ideological subtext. In fact, archival material from the MPAA/PCA Records reveals that the film was deliberately conceived from the outset to be anti-Axis powers. Finally, the article endeavours to explain why a commercial Hollywood production company persisted in its efforts to infiltrate this ideology into the film, at the risk of undermining its box-office performance, and will demonstrate that this was due to the overwhelming mass rejection of The Siege of the Alcazar, a frustrated personal project of Darryl F. Zanuck, which was to be produced by the same company and had a completely opposite ideology.